Assessing the challenges in attaining the predetermined organisational performance objectives in the Gauteng Office of the Premier - Molapho, Makgaba Samuel (University of the Witswatersrand, Johannesburg, 2024)
This research aims to assess the challenges in attaining the predetermined organisational performance objectives in the Gauteng Office of the Premier. In doing so, I have applied the strategy of qualitative research as well as the case study design. This enabled the research to use semi-structured interviews to collect primary data that informs challenges in attaining the predetermined organisational performance objectives in the Gauteng Office of the Premier. The population of this study is Gauteng Office of the Premier and from this population I have sampled 9 participants using a purposive sampling technique. I have located this research in the academic field of organisational performance studies. This field was suitable for my incumbent research due to its aspect connecting to the research problem. Furthermore, I have established attributes of organisational performance and linked them to interpretative frameworks of this research to answer empirical results. The interpretative frameworks of this study are bureaucracy theory, government management frameworks, Government Wide Monitoring and Evaluation (GWM&E) framework, and programme logical model. Using these frameworks as a lens of interpreting research findings, the study indicates that the organisational structure of Gauteng Office of the Premier is not fit for purpose, and it is not approved by the Department of Public Service and Administration (DPSA). As a result, the organisational structure hinders the office of the premier ability to employ human resources that will achieve predetermined objectives. The findings also point out the challenges of data collection, duplication, and alignment of budget to office priorities. Moreover, it was found that stakeholders are non-compliant and do not conform to the implementation of monitoring and evaluation system. As a result, the Gauteng office of the premier is unable to perform because is depended on stakeholders to achieve the office mandate. Lastly, the findings pointed that challenges of attaining predetermined objectives are linked to components of logical model.
Dissertation presented in partial fulfilment for the degree of Master of Management (in the field of Public and Development Sector Monitoring and Evaluation) to the Faculty of Commerce, Law, and Management, University of the Witwatersrand
Keywords: Predetermined organisational performance objectives; Gauteng Office of the Premier; Government management frameworks; Government Wide Monitoring and Evaluation (GWM&E) framework; UCTD; SDG-11: Sustainable cities and communities